Nonlinear deformation of a tapered elastica cantilever due to a tip load - Wang, C.Y. (Archives of Mechanics, 2013)
The nonlinear large deformation of a tip loaded tapered cantilever is studied. Different cross sectional shapes, deformation directions, tapers, base inclinations and end loads are considered. Explicit stability characteristic equations are given. Asymptotic analysis gives good approximations for large tip loads (p > 20). Deformation properties of the tapered cantilever are discussed.